2021
DOI: 10.3390/antiox10020140
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Activity of Citrus Flavanones Mix and Its Stability after In Vitro Simulated Digestion

Abstract: Recently, several studies have highlighted the role of Citrus flavanones in counteracting oxidative stress and inflammatory response in bowel diseases. The aim of study was to identify the most promising Citrus flavanones by a preliminary antioxidant and anti-inflammatory screening by in vitro cell-free assays, and then to mix the most powerful ones in equimolar ratio in order to investigate a potential synergistic activity. The obtained flavanones mix (FM) was then subjected to in vitro simulated digestion to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 49 publications
4
42
0
Order By: Relevance
“…All determinations were performed in triplicate and results were expressed as mean ± SD. Free Radical Scavenging Activity of "Aglianico", "Fiano", and "Greco" grape cane extracts at pH 1.00 (A), 7.00 (B), 13.00 (C), and antioxidant reference compounds. DPPH assay was performed with 5 µg GAE of extracts or pure reference compounds as described in Section 3.4.1.…”
Section: Antioxidant Powermentioning
confidence: 99%
See 1 more Smart Citation
“…All determinations were performed in triplicate and results were expressed as mean ± SD. Free Radical Scavenging Activity of "Aglianico", "Fiano", and "Greco" grape cane extracts at pH 1.00 (A), 7.00 (B), 13.00 (C), and antioxidant reference compounds. DPPH assay was performed with 5 µg GAE of extracts or pure reference compounds as described in Section 3.4.1.…”
Section: Antioxidant Powermentioning
confidence: 99%
“…These molecules, thanks to their well-known strong antioxidant power, are of significant interest for use in the food, cosmetic and pharmaceutical industries [ 12 ]. Furthermore, they possess anti-inflammatory and anti-cancer properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of some pro-inflammatory cytokines can alleviate many inflammatory diseases [47][48][49][50]. It is reported that flavonoids inhibit pro-inflammatory mediators such as cytokines/chemokines, eicosanoids, and adhesion molecules [51,52]. In this sense hesperidin, a flavanone isolated from citrus fruit, has anti-inflammatory and antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean diet comprises a set of foods that commonly feature in the diet of inhabitants from countries bordering the Mediterranean Sea. This is mainly composed of vegetables, fruit, cereals and legumes—the roles of which have been recognized in the prevention of obesity and chronic degenerative diseases, such as diabetes, tumors, hypertension—thus, it represents a healthy model to follow, since a balanced diet combined with a correct lifestyle is the essential basis for our health [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Pomegranate ( Punica granatum L.) juice extract is able to inhibit reactive oxygen species release, increasing the cellular antioxidant response, but also a combination of olive leaf and fruit extracts may be useful to safely reduce hypertension and MetS markers [ 2 , 5 , 6 ].…”
mentioning
confidence: 99%
“…Natural bioactive compounds from natural plants, such as Citrus flavanones, exhibit antioxidant and anti-inflammatory activities in vitro in a synergistic way; in addition, Tuscan bee pollen is a rich source of essential nutrients and potential nutraceutical product [ 3 ]. The origin of the Mediterranean diet is traced back to about 10,000 years ago in the Middle East where wheat, olive oil and wine made up a large part of the crops of this land, to which later, thanks to commercial exchanges, other plants and vegetables were added.…”
mentioning
confidence: 99%